Web-Based Personalized Learning Media for Enhancing Cognitive Abilities of Vocational High School Students in Basic Programming Subject - Damayanti, Tiara Ayu; Prabawa, Harsa Wara; Rahman, Eka Fitrajaya (Universitas Pendidikan Indonesia, 2022)
Every student has different personal needs and characteristics and those must be considered as the factors that must be considered in the learning process. Therefore, appropriate learning methods must be student-centered, otherwise known as personalized learning. This study aims to implement web-based learning media with a personalized learning approach to improve cognitive abilities of vocational school students, measure the effect of media application and student responses to learning media. This study uses a quantitative method with a comparative causal design, and the Whole Life Cycle method is used for media development. The research design used was a one-group pretest-posttest. Web-based learning media with a personalized learning approach that was developed and got a percentage score of 86% or